Measurement and interpretation of fermion-pair production at LEP energies from 130 to 172 GeV - Abreu, P; Adam, W; Adye, T; Adzic, P; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; Amaldi, U; et al. (1999)
The data collected with the DELPHI detector at centre-of-mass energies between 130 and 172 GeV, during LEP operation in 1995 and 1996, have been used to determine the hadronic and leptonic cross-sections and leptonic forward-backward asymmetries. In addition, the cross-section ratios and forward-backward asymmetries for flavour-tagged samples of light (uds), c and b quarks have been measured. No significant deviations from the Standard Model expectations are found. The results are interpreted by performing S-matrix fits to these data and to the data collected previously at the energies near the Z° resonance peak (88-93 GeV). The results are also interpreted in terms of physics beyond the Standard Model: contact interactions, R-parity violating SUSY particle exchange and of possible Z′ bosons.